Selected Methods for Supporting the Growth of Economic Efficiency in Transportation Orders Originating in Electronic Transport Exchanges - Roman STRYJSKI; Waldemar WOŹNIAK; Maciej NIEDZIELA (Communications of International Proceedings, 2020)
The article presents a research problem considered in the context of the analysis and selection of optimisation algorithms which are used to solve the tasks of assigning vehicles to transport orders and measuring their economic efficiency. Two optimisation algorithms were compared and used for the present analysis. The first was the Hungarian algorithm, which is a classic transport algorithm, used in most TMS systems, that is, in the Transportation Management System, the second was an original algorithm, based on heuristic methods and implemented in some selected transport companies under the name: the Improvement Algorithm.
Keywords: Allocation Issue; Heuristic Method; Algorithm; Economic Efficiency